Cross sectional retrospective study on paracetamol post infants’ vaccination - Suleiman, Nurain; Shamsudin, Siti Hadijah; Mohd Rus, Razman; Draman, Samsul (Wolters Kluwer Medknow Publications, 2020)
Introduction: Practice of dispensing Paracetamol (PCM) post infants’ vaccination remains doubtful in Malaysia, thus requiring appropriate regulation measures. Objectives: This research aims to investigate the prevalence of PCM prescribing groups and its associated factors (i.e. gender, age, types and stages of vaccination, concomitant vaccines and drugs and/ vitamins). Materials and Methods: A retrospective cross-sectional study was done for 2011–2017 where the Adverse Events Following Immunization (AEFI) was extracted from Quest 2, Quest 3 and Quest 3+ System of National Pharmaceutical Regulatory Agency (NPRA). The population of vaccinated babies was extracted from the Ministry of Health (MOH) Malaysia official website. The AEFI data was further categorized into (i)AEFI with possibility for PCM to be prescribed and (ii)AEFI with no possibility for PCM to be prescribed. The data was analysed using Microsoft Excel 2013, Simple and Multiple Logistic Regression Tests, SPSS version 22. Results: 359 infants with various AEFI cases reported in 2011–2017. DTaP/Hib/IPV and MMR showed higher prevalence with value of (2.07 and 2.21 respectively) AEFI cases per 100, 000 population than other types of vaccinations meanwhile, the 2 months DTaP/Hib/IPV vaccination showed the highest (3.00) among other age groups. Simple analysis revealed that no factor associated with PCM prescribing groups. Backward Elimination LR Method presented that 3–4 months DTaP/Hib/IPV (95%CI; 0.231, 0.899%; p=0.023) was the associated factor of PCM prescribing groups. 1–5 months Hepatitis B (91.57%), 3–4 months DTaP/Hib/IPV (97.8%), 5–12 months DTaP/ Hib/IPV (95.64%), concomitant vaccines (10.43%) as well as concomitant drugs and/ vitamins (29.45%) were the identified potential cofounders. Conclusion: 2–4 months DTaP/Hib/IPV and 12 months MMR groups were found as the associated factors of PCM prescribing groups, thus PCM post infants’ vaccination may be confined to these groups. The population data for the potential cofounders identified may be collected and analysed for the next research.